Cambodia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting and auditing practices within the corporate sector in Cambodia with reference to the International Financial Reporting Standards (IFRS) issued by the International Accounting Standards Board (IASB), and the International Standards on Auditing (ISA) issued by the International Federation of Accountants (IFAC). This assessment is positioned within the broader context of the Cambodia's institutional framework and capacity needed to ensure the quality of corporate financial reporting Cambodia is putting in place an institutional framework with regard to accounting, auditing, and financial reporting practices. However, institutional weaknesses in regulation, compliance, and enforcement of standards and rules still exist. The accounting and auditing statutory framework suffers from inconsistencies among different laws. Although the national accounting standards and auditing standards are based on IFRS, and ISA, respectively, they appear outmoded and have gaps in comparison with the international equivalents. There are varying compliance gaps in both accounting and auditing practices. These gaps could primarily stem from lack of clearer understanding by professional accountants, inadequate technical capacities of the regulators, absence of implementation guidance, lack of independent oversight of the auditing profession, and shortcomings in professional education and training. There is little awareness of the importance of quality financial information in Cambodia. Financial reporting is driven primarily by complying with requirements of shareholders, obtaining bank loans, and satisfying the taxation regime. Auditing in Cambodia is perceived as an exercise of little value. The law does not outline which standards should be followed in conducting audits. Cambodia's accounting profession is largely dominated by the members of the Association of Chartered Certified Accountants of the United Kingdom. The Kampuchea Institute of Certified Public Accountants and Auditors is in its early stage of development and should be geared to contribute in creating an enabling environment for high-quality corporate financial reporting and auditing practices in the country.